Soft tissue preservation in the Triassic pachypleurosaur Keichousaurus hui: evidence for digestive tract anatomy, diet, and feeding behavior - Li, Ji; Lehrmann, Daniel J.; Luo, Yong-ming; Adams, Thomas L.; Yu, Mei-yi; Liao, Jun-ling; Qin, Yan-jiao; Li, Yu-lan; Wang, Yue (Frontiers in Ecology and Evolution, 2023)
Keichousaurus hui is the most abundant and representative species in Xingyi Biota of South China. Keichousaurus hui has been studied in many aspects, including the functional morphology, osteology, ontogeny, allometric growth, sexual dimorphism, and reproduction. Previous studies have assumed that Keichousaurus’ anteriorly curved teeth were used to impale prey and transport either torn or whole prey to the esophagus. Prey items have been assumed to be small fish or soft bodied invertebrates such as squid and shrimp also represented in the Xingyi Biota. However, there has been no direct evidence for the anatomy of the digestive tract or the diet of Keichousaurus. There are few reports of the soft tissue preservation of Keichousaurus hui. In this study, we present a relatively complete preservation of the digestive tract with food remains in several well-preserved specimens of Keichousaurus hui. By comparing with modern reptiles, we reconstructed the internal distribution and organs composition of the digestive tract of Keichousaurus hui. Through the analysis of the alimentary canal remnants by microscope and X-ray computed microtomography, we infer that Keichousaurus hui is a frequently piscivorous species that usually swallows its prey whole.